Cost-Effectiveness Analysis of Tislelizumab Plus Chemotherapy as First-Line Treatment for Advanced or Metastatic Esophageal Squamous Cell Carcinoma in China - Zhou C; Wei J; Xu K; Lin Y; Zhang L; Li X (Dove Medical Press, 2023)
Chongchong Zhou,1,2,* Jingxuan Wei,1,* Kai Xu,1 Yingtao Lin,3,4 Lingli Zhang,1 Xin Li1,4,5 1Department of Pharmaceutical Regulatory Science and Pharmacoeconomics, School of Pharmacy, Nanjing Medical University, Nanjing, People's Republic of China; 2Department of Research Management, Nanjing Stomatological Hospital, Affiliated Hospital of Medical School, Nanjing University, Nanjing, People's Republic of China; 3Department of Drug Clinical Trial Institution, Fujian Medical University Cancer Hospital, Fujian Cancer Hospital, Fuzhou, People's Republic of China; 4Center for Global Health, School of Public Health, Nanjing Medical University, Nanjing, People's Republic of China; 5Department of Health Policy, School of Health Policy and Management, Nanjing Medical University, Nanjing, People's Republic of China*These authors contributed equally to this workCorrespondence: Xin Li; Lingli Zhang, School of Pharmacy, Nanjing Medical University, No. 101 Longmian Avenue, Jiangning District, Nanjing, Jiangsu, 211166, People's Republic of China, Email xinli@njmu.edu.cn; zhanglingli@njmu.edu.cnBackground: Tislelizumab plus chemotherapy improved overall survival compared to chemotherapy alone, while maintaining an acceptable level of safety. But it's still unclear which strategy is the most cost-effective. The objective of the study was to compare the cost-effectiveness of tislelizumab plus chemotherapy as first-line therapy for patients with advanced or metastatic esophageal squamous cell carcinoma (ESCC) versus chemotherapy alone.Methods: A partitioned survival model with three states was constructed based on the RATIONALE-306 trial. The model's time horizon was ten years, and its cycle was three weeks. Only direct medical costs were considered from the healthcare perspective in China. Calculations were performed on total costs, quality-adjusted life years (QALYs), and incremental cost-effectiveness ratios (ICERs). One-way sensitivity and probabilistic sensitivity analysis (PSA) were performed to determine the uncertainty regarding model parameters.Results: Tislelizumab plus chemotherapy provided 1.35 QALYs for $26,450.77, while chemotherapy alone provided 0.89 QALY for $16,687.15. Compared to chemotherapy alone, tislelizumab had an ICER of $21,062.09/QALY. At the threshold of three times the Chinese GDP per capita ($38,253/QALY), the PSA indicated that tislelizumab had a 96.4% likelihood of being designated cost-effective. At the threshold of 1.5 times the Chinese GDP per capita ($19,126.5/QALY), the PSA indicated that tislelizumab had a probability of 48.7% of being designated cost-effective.Conclusion: Tislelizumab plus chemotherapy as the first treatment for patients with advanced or metastatic ESCC may be a cost-effective option compared to chemotherapy alone at 3 times Chinese GDP per capita.Keywords: esophageal squamous cell carcinoma, cost-effectiveness, partitioned survival model, tislelizumab